Growth And Characterization Of Nanostructured Nickel Oxide Thin Films For Photodetection Applications - Ahmed, Anas Awad Hasan (2020)
The aim of this study was to grow good crystalline quality of NiO thin films over Si substrate for photodetection application. The study was divided into three main parts. The first part focuses on growth of nanostructured NiO thin films using non-reactive RF sputtering technique. XRD analysis showed that with increasing substrate temperature from RT to 100 oC, the crystallite size was increased from 19.14 to 28.20 nm; followed by a decrease to 14.71 nm as the substrate temperature was increased to 200 oC. The further increase of the temperature to 300 oC, resulted in decomposition of NiO film into Ni. With the increase of the RF power from 150 to 200 W and the film thickness from 350 to 640 nm, the crystallite size was improved from 17.46 to 28.20 nm and from 28.20 to 29.66 nm, respectively; however, the crystalline quality of the films was degraded when the RF power and film thickness were further increased to 300 W and 920 nm, respectively. NiO film deposited at 100 oC, RF power 200 W and thickness 640 nm showed optimal crystalline quality with crystallite size value of 29.66 nm for which it was then selected for photodetection application. The second part of this work studies the growth of nanostructured NiO films using sol-gel spin coating technique. NiO film grown at stabilizer molar ratio of 0:1 suffered from severe cracks. The increase in the molar ratio to 1:1 resulted in cracks-free film. NiO film coated at molar ratio of 1:1 was annealed at different temperatures (300 to 650 oC).